Role of Sonography in Prenatal Evaluation of Placenta Accreta - Rahila Usman; Sumayya Fatima; Sadia Rashid; Sehrish Mehmood; Kashif Shazlee; Kamran Hamid (Journal of Bahria University Medical and Dental College)
Objective: To evaluate the diagnostic accuracy of gray scale and doppler examination in antenatal diagnosis of placenta accreta.